An expenditure estimate of Irish national income in 1907 - Bielenberg, Andy; O'Mahony, Patrick (Economic & Social Studies, 1998)
In order to compare Ireland's GDP per capita to other countries in the early twentieth century, a new expenditure based estimate for 1907 is presented in this article. Since it broadly adopts Feinstein's method for estimating UK GDP, it is more compatible with the UK figures than previous estimates and therefore provides a better benchmark for comparison with other countries. In general expenditure based GDP estimates tend to come out higher than income or output based estimates. If the latter methods are adopted for Ireland and compared to Feinstein's figures for the UK, this will tend to understate Irish performance. This paper attempts to reconcile this problem by adopting a more compatible methodology; it concludes that Ireland's economic performance was better than earlier estimates suggest.
Keywords: Economic history; National income; Ireland; GDP